Evaluation of plant growth promoting and antifungal activities of Talaromyces flavus (NAIMCC-F- 01948) against Sclerotium rolfsii - K. SUNAR and P.L. DEY, B.N. CHAKRABORTY*, U. CHAKRABORTY (Indian Phytopathology, 2012)
Talaromyces flavus belonging to the family Trichocomaceae of the Ascomycota was isolated from rhizosphere soil of paddy. Light microscopic and scanning electron microscopy revealed rough walled and spiny characters of the ascospores. This fungus exhibited phosphate solubilizing activity when screened on Pikovskaya’s agar medium and could solubilize 849 mg/l of tricalcium and 374 mg/l of rock phosphate respectively after ten days of incubation which was comparatively higher than other tested isolates of Aspergillus niger, A. melleus and A. clavatus. Ability of T. flavus as amendment in the soil to promote growth activities of different crops was tested on Triticum aestivum, Pisum sativum, Vigna radiata and Camellia sinensis in glass house conditions. T. flavus increased phosphatase activities in the soil. It increased in leaf and root phosphate contents and decreased in total soil phosphate content. T. flavus inhibited sclerotial germination of plant pathogenic fungus Sclerotium rolfsii and could enhance seedling germination and survival of Vigna radiata which had been inhibited by S. rolfsii in greenhouse experiments. ITS-PCR of the ribosomal DNA of T. flavus was sequenced for identification.